Exergaming delivery of a balance and fall prevention program for older adults: A feasibility study. (December 2022) - Ren, Ivy; Rozanski, Gabriela; Fernandez, Naiara; Zabala, Amaia; Ramos, Amaia; Arrinda, Ismene; Tabacof, Laura; Putrino, David
Objective: Older adults are at high risk of falls and this problem calls for efficient and scalable interventions. This study investigated whether a motion capture system paired with balance training exergaming software is a feasible strategy to deliver therapeutic exercise to older adults in an aged care facility. Methods: This study analyzed data from a quality improvement rehabilitation initiative. Two convenience samples of older adults were included: a usual care group ( n  = 12), admitted to a rehabilitation hospital and receiving standard in-patient therapy 5×/week and the Evolv group ( n  = 12), admitted to an aged care facility, prescribed exergaming 3×/week. All participants performed 30-minute exercise sessions based on a fall prevention program over 3 months. The Short Physical Performance Battery (SPPB) and Tinetti Performance Oriented Mobility Assessment test were administered pre- and post-treatment. Results: No adverse events were recorded during the interventions. Mean SPPB increase for Evolv participants was 2.25 ± 1.35 ( p  < .001, CI for mean = 1.39 to 3.11, d  = 1.66), compared with a non-significant change in the usual care group (mean increase = 2.25 ± 3.82, p  = .066, CI for mean = −0.18 to 4.68, d  = 0.59). Tinetti improvement was significant for the individuals receiving usual care (3.83 ± 2.82, p  = .012, CI for mean = 1.01 to 6.66, d  = 0.86) but there were no significant between-group differences in outcomes. Conclusions: Exergaming with the Evolv system for balance and strength training may be a feasible strategy to improve physical function for older adults recovering in an aged care facility.